Synthesis, Characterization and Dye-Sensitized Solar Cell Application of a Novel Symmetric Diphenylpyran Dye with Dual Rhodamine-3-acetic Acid Anchors. (June 2020) - Wang, Xinxin; Bolag, Altan; Yun, Wu; Zhang, Xiaoying; Bao, Tana; Ning, Jun; Alata, Hexig; Ojiyed, Tegus
Abstract: With simple three-step method, a new symmetrical metal free organic diphenylpyran dye containing dual rhodamine-3-acetic acid anchors was successfully synthesized, characterized and applied to dye-sensitized solar cells (DSSC). The dye has saturated methylene in its acceptor part, which makes the electron withdrawing group and the anchor group cannot be conjugated well. In addition, the exhibits lower molar extinction coefficients of the dye and its blue-shifted absorption spectrum also influenced the light capture ability. The resulting weaker intramolecular charge transfer and the electron coupling effect of the dye hindered the dye charge injection and shorten the electron lifetime, leading to an average power conversion efficiency of 0.65 % ( Jsc = 2.32 mA cm −2, Voc = 448 mV and FF = 0.63). Further design of an efficient dye molecule needs efficient conjugation between the electron-withdrawing group and anchoring group, as well as an effective light harvest capability.